Numerical Simulation on Heat Recovery Efficiency of Different Working Fluids in High-Temperature Rock Mass - Xu Dong; Haozhe Geng; Guan Hao; Pan Li; Yi Teng; Wen Zhang (Geofluids)
It is of great significance for the sustainable development of global energy to develop hot dry rock (HDR) geothermal resources by using enhanced geothermal system (EGS) technology. Different working fluids in EGS have different heat recovery efficiencies. Therefore, this paper takes water and CO2 as the heat-carrying media and establishes a thermal hydraulic mechanical coupling model to simulate the heat recovery process in high-temperature rock mass. By considering the different confining pressures, rock temperature, and injection pressure, the advantages of H2O-EGS and CO2-EGS are obtained. The results show that with the increase of confining pressure, the heat recovery efficiency of water is significantly higher than that of CO2, but at higher reservoir temperature, CO2 has more advantages as a heat-carrying medium. The net heat extraction rate will increase with the increase of injection pressure, which indicates that the mass flow rate plays a leading role in the heat recovery process and increases the injection pressure of fluid which is more conducive to the thermal recovery of EGS. This study will provide a technical guidance for thermal energy exploitation of hot dry rock under different geological conditions.